1983
DOI: 10.1113/jphysiol.1983.sp014893
|View full text |Cite
|
Sign up to set email alerts
|

Ionic movements through light‐sensitive channels of toad rods.

Abstract: SUMMARY1. Electrical photoresponses of rods in the isolated toad retina were recorded during ionic manipulations of the Na+-free extracellular medium.2. In the presence of a concentration of external Ca2+ above 10-5 M, voltage photoresponses were observed only in the presence of external Na+ or Li+.3. When external Ca2+ was reduced below 10-6 M, voltage photoresponses of normal polarity could be detected even in the absence of Na+ or Li+, but in the presence of external Mg2+.4. In the presence of normal extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

1986
1986
1994
1994

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 65 publications
(39 citation statements)
references
References 20 publications
3
36
0
Order By: Relevance
“…One question is whether in normal conditions a significant outward K+ movement also exists through the light-sensitive conductance in darkness. We think this is not very likely, even though the conductance is permeable to K+ (Woodruff, Fain & Bastian, 1982;Capovilla et al 1983;Yau & Nakatani, 1984a;Hodgkin et al 1985). From the results described here, we know that the movements of ions through the light-sensitive conductance do not obey independence (see also Capovilla et al 1983), so that normally with a steady influx of Na+, Ca2+ and Mg2+, little K+ is likely to be able to move out.…”
Section: Composition Of the Dark Currentmentioning
confidence: 81%
“…One question is whether in normal conditions a significant outward K+ movement also exists through the light-sensitive conductance in darkness. We think this is not very likely, even though the conductance is permeable to K+ (Woodruff, Fain & Bastian, 1982;Capovilla et al 1983;Yau & Nakatani, 1984a;Hodgkin et al 1985). From the results described here, we know that the movements of ions through the light-sensitive conductance do not obey independence (see also Capovilla et al 1983), so that normally with a steady influx of Na+, Ca2+ and Mg2+, little K+ is likely to be able to move out.…”
Section: Composition Of the Dark Currentmentioning
confidence: 81%
“…Alternatively it is possible that lowered calcium functions by decreasing the activity of the phosphodiesterase (Bownds, 1980), either directly or through modification of earlier biochemical steps in the transduction pathway (Lamb et al 1985b). Whatever the mechanism, one result of an elevated dark current would be an elevated influx of Ca2+, because the light-sensitive channels are permeable to Ca2+ 345 T. D. LAMB, H. R. MATTHEWS AND V. TORRE and other divalent ions (Capovilla, Caretta, Cervetto & Torre, 1983;Hodgkin et al 1984;Yau & Nakatani, 1984a, b). This would tend to oppose the reduction in cytoplasmic free calcium concentration, thus completing the negative feed-back loop.…”
Section: Cytoplasmic Free Calcium Concentrationmentioning
confidence: 99%
“…The selectivity of the cGMP-activated channel to alkali monovalent cations and to divalent cations has already been studied both in intact retinal rods, by changing solutions at the extracellular side of the cell (Capovilla, Caretta, Cervetto & Torre, 1983;Hodgkin, McNaughton & Nunn, 1985;Nakatani & Yau, 1988;Menini, Rispoli & Torre, 1988) and in excised inside-out patches by changing internal cations (Fesenko et al 1985;Nunn, 1987;Furman & Tanaka, 1990;Menini 1990;Colamartino, Menini & Torre, 1991). It was found that the cGMP-activated channel is a poorly selective cation channel with different selectivity properties from those of other channels.…”
Section: Introductionmentioning
confidence: 99%